The Role of Acetaldehyde in the Increased Acceptance of Ethanol after Prenatal Ethanol Exposure - Gaztañaga, Mirari; Angulo-Alcalde, Asier; Spear, Norman E.; Chotro, M. Gabriela (Frontiers in Behavioral Neuroscience, 2017)
Recent studies show that acetaldehyde, the first metabolite in the oxidation of ethanol, can be responsible for both, the appetitive and the aversive effects produced by ethanol intoxication. More specifically, it has been hypothesized that acetaldehyde produced in the periphery by the liver is responsible for the aversive effects of ethanol, while the appetitive effects relate to the acetaldehyde produced centrally through the catalase system. On the other hand, from studies in our and other laboratories, it is known that ethanol exposure during the last gestational days consistently enhances the postnatal acceptance of ethanol when measured during early ontogeny in the rat. This increased liking of ethanol is a conditioned appetitive response acquired by the fetus by the association of ethanol’s flavor and an appetitive reinforcer. Although this reinforcer has not yet been fully identified, one possibility points to acetaldehyde produced centrally in the fetus as a likely candidate. This hypothesis is supported by data showing that very early in the rat’s ontogeny brain catalases are functional, while the liver’s enzymatic system is still immature. In this study, rat dams were administered on gestational days 17-20 with water or ethanol, together with an acetaldehyde-sequestering agent (D-penicillamine). The offspring’s responses to ethanol was then assessed at different postnatal stages with procedures adequate for each developmental stage: on day 1, using the “odor crawling locomotion test” to measure ethanol’s odor attractiveness; on day 5, in an operant conditioning procedure with ethanol as the reinforcer; and on day 14 in an ethanol intake test. Results show that the absence of acetaldehyde during prenatal ethanol exposure impeded the observation of the increased acceptance of ethanol at any age. This seems to confirm the crucial role of acetaldehyde as a reinforcer in the appetitive learning occurring during prenatal ethanol exposure.